Zonal velocity of the equatorial plasma bubbles over Kolhapur, India - D. P. Nade; A. K. Sharma; S. S. Nikte; P. T. Patil; R. N. Ghodpage; M. V. Rokade; S. Gurubaran; A. Taori; Y. Sahai (Annales Geophysicae, 2013)
This paper presents the observations of zonal drift velocities of equatorial ionospheric plasma bubbles and their comparison with model values. These velocities are determined by nightglow OI 630.0 nm images. The nightglow observations have been carried out from the low latitude station Kolhapur (16.8° N, 74.2° E; 10.6° N dip lat.) during clear moonless nights. Herein we have presented the drift velocities of equatorial plasma bubbles for the period of February–April 2011. Out of 80 nights, 39 showed the occurrence of equatorial plasma bubbles (49%). These 39 nights correspond to magnetically quiet days (ΣKp < 26). The average eastward zonal velocities (112 ± 10 m s−1) of equatorial plasma bubbles increased from evening sector to 21:00 IST (Indian Standard Time = Universal Time + 05:30:00 h), reach maximum about 165 ± 30 m s−1 and then decreases with time. The calculated velocities are in good agreement with that of recently reported values obtained with models with occasional differences; possible mechanisms of which are discussed.